2007
DOI: 10.1038/sj.eye.6702737
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of timolol on endothelial cells and its relevance for glaucoma course

Abstract: Purpose A growing evidence in the scientific literature suggests that oxidative damage plays a pathogenic role in primary open-angle glaucoma. Therefore, it is of interest to test whether drugs effective against glaucoma display antioxidant activity. We test the hypothesis that the classic b-blocker therapy for glaucoma with timolol involves the activation of antioxidant protective mechanisms towards endothelial cells. Methods Oxidative stress was induced in cultured human endothelial cells by iron/ ascorbate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 61 publications
1
22
0
1
Order By: Relevance
“…36 The TM is a complex cellular system that increases the contact surface between the endothelium and AH. 1 The TM is responsible for the AH outflow from the AC and Schlemm's canal. 33,35 The TM undergoes a progressive time-related decline in the number of cells until a dysfunction of the entire region occurs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 The TM is a complex cellular system that increases the contact surface between the endothelium and AH. 1 The TM is responsible for the AH outflow from the AC and Schlemm's canal. 33,35 The TM undergoes a progressive time-related decline in the number of cells until a dysfunction of the entire region occurs.…”
Section: Discussionmentioning
confidence: 99%
“…1 AH is secreted in the posterior chamber by the ciliary body and leaves the AC via two routes: the conventional (anterior) route is the through the TM, and the unconventional (posterior) route is through the uveoscleral pathway. 2 Uveoscleral outflow contributes to approximately 30% of the total amount of AH drainage.…”
mentioning
confidence: 99%
“…However timolol preserves NO inside the erythrocyte will not favoured the formation of peroxinitrite in an oxygen reactive stress external environment. The antioxidant ability of timolol was evidenced in vitro in endothelial cells and neutrophils, as well in vivo in newborn rats under oxygen induced retinopathy [26][27][28].…”
Section: Resultsmentioning
confidence: 99%
“…5 Other studies have also shown that timolol protects from free radical-induced apoptosis because of its antioxidant potential. 6 We may suggest that research studies in tear samples may help in deciding the oxidative potential of diverse topical glaucoma medications much more than the aqueous humor or vitreous body samples.…”
mentioning
confidence: 99%